First Measurement of 𝐴 = 4 Hypernuclei and Antihypernuclei at the LHC - Trubnikov, Vyacheslav; The ALICE collaboration (Physical Review Letters, 2025)
In this Letter, the first evidence of the _Λ^4He antihydrogen hypernucleus is presented, along with the first measurement at the LHC of the production of (anti)hypernuclei with mass number A = 4, specifically (anti)_Λ^4H and (anti)_Λ^4He. In addition, the antiparticle-to-particle ratios for both hypernuclei (_Λ^4H / _Λ^4H and _Λ^4He / _Λ^4He) are shown, which are sensitive to the baryochemical potential of the strongly interacting matter created in heavy-ion collisions. The results are obtained from a data sample of central Pb-Pb collisions, collected during the 2018 LHC data taking at a center-of-mass energy per nucleon pair of √s_NN = 5.02 TeV. The presence of (anti)_Λ^4H and (anti)_Λ^4He excited states is expected to strongly enhance the production yield of these hypernuclei. The yield values exhibit a combined deviation of 3.3σ from the theoretical ground-state-only expectation, while the inclusion of the excited states in the calculations leads to an agreement within 0.6σ with the present measurements. Additionally, the measured (anti)_Λ^4H and (anti)_Λ^4He masses are compatible with the world-average values within the uncertainties.